Maternal outcome of selective feticide due to fetal anomaly in late trimester: A retrospective 10 years' experience in Taiwan. Issue 2 (19th August 2021) - Sung, Chen-Ai; Lin, Tzu-Yi; Lee, Han-Ni; Chan, Kok-Seong; Hung, Tai-Ho; Shaw, Steven W.
Abstract : Background: Feticide was suggested to avoid delivering children with abnormalities. Recently, twin pregnancies have increased. Selective feticide was proposed to achieve a good outcome of pregnancy. This study aimed to evaluate the performance of feticide in twin pregnancy with fetal anomaly. Methods: This was a retrospective study enrolled from 2009 to 2018. A total of 68 pregnancies with fetal anomalies received feticide. Potassium chloride was injected into the left ventricle to induce fetal asystole. Maternal and fetal characteristics of 16 dichorionic twins were documented to compare before and after 24th gestational week. Results: All pregnant women received feticide without any maternal or fetal complication. The reasons for choosing feticide were divided into four groups, including morphologic defect (61.8%), genetic-chromosomal abnormality (30.9%), obstetrical complication (5.9%), and maternal request (1.5%). Mean gestational age at delivery was significantly higher in dichorionic twins who underwent selective feticide before than after 24th gestational week (36.7 vs 33.4, p = 0.04). Conclusion: Intracardiac injection of potassium chloride was effective for feticide and safe for mothers and fetuses. Selective feticide served as an alternative approach for twin pregnancy with fetal anomaly after sufficient discussion.